Pseudocapacitive charge storage in thin nanobelts - Kunwar, Ria; Harilal, Midhun; Krishnan, Syam G.; Pal, Bhupender; Izan Izwan, Misnon; Mariappan, C. R.; Ezema, Fabian I.; Elim, Hendry Izaac; Yang, Chun-Chen; Rajan, Jose (Springer, 2019)
This article reports that extremely thin nanobelts (thickness ~ 10 nm) exhibit pseudocapacitive (PC) charge storage in the asymmetric supercapacitor (ASC) configuration, while show battery-type charge storage in their single electrodes. Two types of nanobelts, viz. NiO–Co3O4 hybrid and spinal-type NiCo2O4, developed by electrospinning technique are used in this work. The charge storage behaviour of the nanobelts is benchmarked against their binary metal oxide nanowires, i.e., NiO and Co3O4, as well as a hybrid of similar chemistry, CuO–Co3O4. The nanobelts have thickness of ~ 10 nm and width ~ 200 nm, whereas the nanowires have diameter of ~ 100 nm. Clear differences in charge storage behaviours are observed in NiO–Co3O4 hybrid nanobelts based ASCs compared to those fabricated using the other materials—the former showed capacitive behaviour whereas the others revealed battery-type discharge behaviour. Origin of pseudocapacitance in nanobelts based ASCs is shown to arise from their nanobelts morphology with thickness less than typical electron diffusion lengths (~ 20 nm). Among all the five type of devices fabricated, the NiO–Co3O4 hybrid ASCs exhibited the highest specific energy, specific power and cycling stability.